¿Qué es la gestión del cambio? (Assemble You, 2022)
Welcome to Audio Learning by Assemble You. On average, organizations today have experienced at least five major company-wide changes in the last three years, and nearly 75% expect to increase the types of major change initiatives they will undertake in the next three years. But about half of change initiatives fail, while only 34% report clear success. In this recording, we develop what ""change management"" really is, by looking at some of the most well-known methodologies. We also give you tips to be part of the 34% who are successful in their change initiatives. Learning Objectives The first objective of this lesson is to develop a clear understanding of what change management really is The second objective will focus on how to guide a team through a change management process The third in the list of objectives part of this lesson is to understand how you deal with change in your own work or area of influence